2017
DOI: 10.3329/kyamcj.v7i2.33837
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Electrolyte Imbalance in Asphyxiated Neonates

Abstract: In

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
3
3
0
Order By: Relevance
“…It was similar to the findings observed by Mishra et al, [29] Najaf Masood et al, [26] Rahman F et al [27] and Prodhan et al [30] in their studies. Gupta et al (2005) [31] in their study has shown that severity of renal function abnormality correlates well with degree of asphyxia.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…It was similar to the findings observed by Mishra et al, [29] Najaf Masood et al, [26] Rahman F et al [27] and Prodhan et al [30] in their studies. Gupta et al (2005) [31] in their study has shown that severity of renal function abnormality correlates well with degree of asphyxia.…”
Section: Discussionsupporting
confidence: 82%
“…Similar result was observed by Rahman F and Siddique MAB et al [27] in the year 2017. Study by G Joag et al (2017) [28] showed similar result of decreased mean value of serum sodium, serum calcium and serum glucose in asphyxiated newborns, which had positive correlation with the severity of birth asphyxia.…”
Section: Discussionsupporting
confidence: 80%
“…Our results are different from previous studies. In a study by Rehman F et al, the researchers found that hyponatremia is present in 30% of the asphyxiated babies while only 15% in total population (p value < 0.001) 15 . Shamaoon et al, discovered through a cross sectionals study that blood sodium was 137.71 1.69mg/dl (normal range) and concluded that mean serum electrolyte levels in neonates with perinatal birth asphyxia and mild hypoxic ischemic encephalopathy were within normal range.…”
Section: Discussionmentioning
confidence: 96%
“…After approval of study for local ethics committee, this Case control study was conducted in the Department of Pediatrics in collaboration with Department of Obstetrics & Gynecology, Aziz Bhatti Shaheed Teaching Hospital Gujrat from 1 st July 2019 to 30 th April 2021. Calculated sample size was 268 (134 cases and 134 controls) by taking prevalence of hyponatremia as 30.1% patients and 15% in control, 15 at 95% confidence interval and 80% power of study. For both cases and controls full term babies (>37 weeks) of either gender were included only as determined by hospital antenatal records.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation